ANALISIS KELEMAHAN PENEGAKAN HUKUM TERHADAP PRAKTIK KORUPSI DIGITAL PADA LEMBAGA PUBLIK - Nisrina Fatin (Journal of Law and Justice, 2025)
This study aims to analyze regulatory weaknesses and the capacity of law enforcement officials in addressing digital corruption practices in public institutions, particularly related to manipulation of e-procurement systems, data misuse on egovernment platforms, and illegal non-cash transactions through digital financial instruments and crypto assets. The approach used is qualitative-descriptive, using desk study and document analysis methods, including scientific literature, laws and regulations, institutional reports (such as those from the Corruption Eradication Commission (KPK) and the Supreme Audit Agency (BPK), and actual case studies, such as corruption in the e-KTP (e-KTP) and BTS (telephone communication and communication technology) projects. Data were analyzed through data reduction, thematic categorization, and contextual interpretation of legal sources and previous research on digital governance and corruption eradication. The results indicate that digital corruption operates through data and system manipulation, algorithmic collusion in e-procurement, and abuse of internal access. This is exacerbated by the absence of specific regulations on digital corruption, limited cyber forensics, weak coordination between law enforcement agencies, and a permissive legal culture. This situation creates impunity for perpetrators, undermines public trust in egovernment, and hinders the SPBE-based bureaucratic reform agenda. Therefore, a dedicated legal framework, strengthened digital forensic capacity, and the integration of national law enforcement data platforms are needed.